Contextual challenges in research ethics and quality of research - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2020)
Context, issues and challenges are different in different set up globally. Research and ethics appear to be challenged by ignorance, scarcity, formality and business. Non-research beaurocratic planning and management results in ethically challenged substandard product as the ethics and procedures are not legally binding. Structured training, capacity build up and resource mobilization would be the preliminary solutions.